Ethnomathematics-Based Test Instrument for Assesing Mathematical Process Skills of Seventh-Grade Junior High School - Cahyani, Anisa Eka; Kamid; Ramalisa, Yelli (Desimal: Jurnal Matematika, 2026)
This study aimed to develop and evaluate an ethnomathematics-based test instrument for assessing seventh-grade students’ mathematical process skills in algebraic expressions. The study employed a Research and Development design using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The research was conducted at SMP Negeri 9 Kota Jambi, Indonesia, involving one mathematics teacher, nine students in the small-group trial, and twenty-six students in the field trial. The developed instrument consisted of ten essay items integrating algebraic expressions with Jambi ethnomathematical contexts and measuring five indicators of mathematical process skills: observing, classifying, identifying relationships, calculating, and communicating results. Data were collected through expert validation sheets, practicality questionnaires, student response questionnaires, students’ written answers, and documentation. The results showed that the instrument obtained an expert validation score of 88.39%, indicating a very valid category. The practicality score reached 95.45% from the teacher and 81.71% from students, indicating that the instrument was feasible for classroom use. Empirical item validity analysis showed that all ten items were valid, with r-count values exceeding the r-table value of 0.367. Reliability analysis produced a Cronbach’s alpha coefficient of 0.846, indicating high internal consistency. Student response results reached 85.87%, showing positive acceptance of the instrument. Field implementation also revealed that most students still demonstrated low mathematical process skills in contextual algebra tasks. These findings indicate that the developed instrument is valid, practical, reliable, and appropriate for diagnosing students’ mathematical process skills through culturally meaningful algebra assessment.